Low power laser photobiomodulation therapy in radiotherapy-induced oral complications: a case report - Casco, Dylan (2024)
Oropharyngeal cancer is one of the most common malignant tumors in the head and neck, and among its most frequent complications is oral mucositis, a common result of radiotherapy treatments in this region. Despite its high incidence, no consensus has yet been reached on its therapeutic management. In this context, photobiomodulation with low power laser is presented as a promising alternative, since it does not produce significant adverse effects and facilitates both healing and analgesia in the affected areas, thus improving the patient's quality of life. During the clinical examination of this case report, ulcers were observed on the jugal mucosa on both sides, as well as a lesion with fibrinoleukocytic coating on the posterior right lateral border, which, together with the patient's clinical record, allowed establishing the diagnosis of oral mucositis. For the management of this condition, low power laser photobiomodulation was applied in a total of five sessions, aimed at reducing pain, favoring ulcer healing and treating hyposalivation. At the end of the therapeutic cycle, the patient no longer had ulcers in the oral cavity, the patient reported having recovered his/her sense of taste and there was evidence of an improvement in salivary production. These results highlight the efficacy of photobiomodulation, since it not only relieves the symptoms almost immediately, but also, being a minimally invasive procedure with no known adverse effects, it becomes a valuable tool for the management of oral complications in oncologic patients.